Etherington duality breaking: gravitational lensing in non-metric space-times versus intrinsic alignments - Giesel, Eileen; Ghosh, Basundhara; Schäfer, Björn Malte (Monthly notices of the Royal Astronomical Society, 2023)
The Etherington distance duality relation is well-established for metric theories of gravity, and confirms the duality between the luminosity distance and the angular diameter distance through the conservation of surface brightness. A violation of the Etherington distance duality due to lensing in a non-metric space-time would lead to fluctuations in surface brightness of galaxies. Likewise, fluctuations of the surface brightness can arise in classical astrophysics as a consequence of intrinsic tidal interaction of galaxies with their environment. Therefore, we study these in two cases in detail: First, for intrinsic size fluctuations and the resulting changes in surface brightness, and secondly, for an area-metric space-time as an example of a non-metric space-time, where the distance duality relation itself acquires modifications. The aim of this work is to quantify whether a surface brightness fluctuation effect due to area-metric gravity would be resolvable compared to the similar effect caused by intrinsic alignment. We thus compare the auto- and cross-correlations of the angular spectra in these two cases and show that the fluctuations in intrinsic brightness can potentially be measured with a cumulative signal-to-noise ratio Σ(ℓ) ≥ 3 in a Euclid-like survey. The measurement in area-metric space-times, however, depends on the specific parameter choices, which also determine the shape and amplitude of the spectra. While lensing surveys do have sensitivity to lensing-induced surface brightness fluctuations in area-metric space-times, the measurement does not seem to be possible for natural values of the Etherington-breaking parameters.
Online veröffentlicht 2022 November 25
Gesehen am 27.03.2023